The regional tectonism of the gneisses of part of Namaqualand - Joubert, P (Not Specified, 2024)
A reconnaissance survey of the gneisses of an area some 12,000 km² in extent was conducted in order to determine the geology of the country between the existing geological maps of Bitterfontein in the south and the Richtersveld in the north. The basal rocks are augen gneisses overlain by pink gneisses in the east, succeeded in ascending order by leptites, aluminous rocks; quartzites and mafic gneisses. The paragneisses accumulated before ±2,600 My ago and have been folded and sheared during three events of deformation, each consisting of several episodes with accompanying metamorphism. The earliest recognisable deformation which resulted in the tectonic banding was followed, prior to ±1850 My ago, by isoclinal folding and the associated metamorphism is recorded by zones of distinctive mineral assemblages ranging from greenschist facies at the coast to granulite facies in the east. Subsequent east-west folds, commonly monoclinal in style, with concomitant shearing and tectonic sliding, are responsible for the present prevalent direction of strike of the banding and at the same time large interference structures developed. The first event culminated in the emplacement of granites and pegmatites when open folds formed. The pegmatites occur along an east-west belt to the north of the present area, separating the Namaqualand gneisses from the less-recrystallised rocks farther north. This thermal event, thought to be responsible for the generation of much cordierite as well as wollastonite, probably resulted in the prevalent ±1000 My age returned by the rocks in Namaqualand. During the second event shearing took place under amphibolite- facies metamorphic conditions and the basal part of the Stinkfontein Formation was deposited, probably ±900 My ago, along a north-south trough near the present coast. Large phyllonite zones developed during deformation of the third event when the Upper Stinkfontein Formation accumulated in basins oblique to the strike of the basal sediments and where vertical tectonics in the floor caused gravitational gliding of the sediments. Numerous mafic dykes (±870 My), supplying the volcanic material interbedded with the sediments, were intruded in the coastal regions. The Richtersveld granites (±850 My) were emplaced and the thermal effects recorded by the generation of new minerals. The Nama sediments (±600 My) were deposited and followed by rejuvenation of movement along existing north-south lines of structural weakness. East-west fractures with dolerites (190-150 My) emplaced along them, developed and were followed by strong north-south fracturing resulting in the complicated horst-like structure of the Kamiesberg.